Excited-State Cis and Trans Pt(IV) Diamine Anticancer Complexes - Shi, Huayun; Kasparkova, Jana; Ponte, Fortuna; Kostrhunova, Hana; Clarkson, Guy J; Sicilia, Emilia; Brabec, Viktor; Sadler, Peter J (Inorganic chemistry, 2025)
Classical structure-activity relationships for square-planar Pt(II) anticancer complexes were based on the activity of cis-[PtCl2(NH3)2] (cisplatin) and inactivity of the trans isomer. Many other families of cis-diamine complexes and analogous octahedral Pt(IV) prodrugs are active. Here, we report the chemical and biological activities of isomeric photoactivatable cis,trans,cis- and all-trans-[Pt(N3)2(OH)2(MNZ)2] complexes (MNZ = metronidazole, 1-(2-hydroxyethyl)-2-methyl-5-nitroimidazole). While both are relatively nontoxic in the ground state, only the all-trans isomer is cytotoxic toward bladder cancer cells on excitation with visible light and under hypoxia. Studies of DNA interstrand cross-links and photocytotoxicity toward wild-type and nucleotide-excision-repair deficient cells suggest that, unlike cisplatin, DNA is not the major target site of these isomers. Differences in photoactivation pathways were also explored using time-dependent DFT calculations. The key differences between the isomers on irradiation are the more rapid photoactivation of the all-trans complex, generation of azidyl radicals, retention of its metronidazole ligands, higher accumulation in cancer cells, binding to DNA, RNA, and proteins, and induction of apoptosis and mitochondrial membrane damages. These findings provide a basis for the design of future photochemotherapeutic platinum anticancer prodrugs.
Keywords: molekulární struktura; vztahy mezi strukturou a aktivitou; diaminy; Molecular Structure; screeningové testy protinádorových léčiv; teorie funkcionálu hustoty; Organoplatinum Compounds; Density Functional Theory; nádorové buněčné linie; lidé; protinádorové látky; organoplatinové sloučeniny; Diamines; Cell Line, Tumor; Humans; Structure-Activity Relationship; Antineoplastic Agents; Drug Screening Assays, Antitumor